The Expression Patterns of cGAS and STING as Potential Diagnostic Markers in Gastric Cancer (Journal of Pharmaceutical Negative Results, 2022)
Objective: Gastric cancer (GC) is one of the key causes of cancer-related mortality throughout the world. The cGAS–STING pathway is described as a potential mechanism in cancer immunity and inflammation-mediated tumorigenesis. Accumulating evidence indicate that cGAS–STING pathway is positively related to cancer progression. However, detailed insight into the role of cGAS–STING pathway require further studies. Therefore, understanding the detailed molecular mechanism in the development and progression of GC is of great importance. In the present study, we aimed to evaluate the expression patterns of cGAS and STING and its association with clinicopathological characteristics in gastric cancer patients.Materials and Methods: The expression of two candidate genes, including cGAS and STING were evaluated in tumor tissue samples, normal tissue adjacent to the tumor (NAT) biopsies of fifty new case GC patients by PCR method. PBMCs were isolated from forty GC patients and twenty-five non-cancer subjects as the control group. The expression of cGAS and STING in PBMC samples of both GC patients and control group was also evaluated.Results: Our results demonstrated a significant increase in cGAS expression along with a non-significant increase in STING expression in tumor samples compared to NAT samples. The expression of cGAS and STING in PBMC samples of GC patients represented a non-significant decrease compared to the control group.Conclusion: Our findings could provide detailed insights into the role of the cGAS and STING expression in the progression of GC and contribute to the development of novel therapeutic strategies for GC treatment.